An etnographic study of elementary education in the rural area of Dompu county, the province of West Nusa Tenggara - Nurrahmah Nurrahmah; Zamroni Zamroni; Sumarno Sumarno (Universitas Negeri Yogyakarta, 2016)
The study aims to describe: (1) public service for elementary education in rural areas; (2) the meaning of education and the implementation of elementary education in the people of rural areas; and (3) the life and meaning of poverty for people of rural areas. The study was etnographic research. The subjects were the providers and users of educational service. The research concludes that: (1) educational service in rural areas has not been coordinated and integrated both vertically and horizontally, so that the service elements have not been maximum in providing educational service; (2) the implementation of education is influenced by the surrounding environments (policy, community, and nature) so that its condition or the problems emerging in the lower level is a reflection of that in the upper level. People in rural areas regard education as a symbol of profession and self-actualization within the children's selves in order that the children would show respect to their parents, would not destroy the nature, have noble characteristics and be smart persons for their own sake in the future; (3) physically people in rural areas might be described as a community that lacks facilities including transportation, highway systems, water, electricity, and market for trading the harvest. On the other hand, mentally, people in rural areas might be described as a community that is fond of having aids, enjoys the final products, is lazy and dependent on the nature. People in rural areas regard their poverty based on physical indicators (the possession of luxurious goods, rice fields, livestock, income, and housings) and non-physical indicators (the dependency on the nature and absence of education).